The anion chemistry of transition metal oxides and oxychlorides - Dixon, E (2011)
This investigation is based on the topotactic reduction reactions of 3 sets of phases: La₁-ₓSrₓMnO₃ (0.6 ≤ x ≤ 1), La₁-ₓCaₓMnO₃ (0.6 ≤ x ≤ 1) and Sr₃Fe₂-ₓCoₓO₅Cl₂ (0 ≤ x ≤ 1). The topotactic reduction reactions of La₁-ₓSrₓMnO₃ (0.6 ≤ x ≤ 1) perovskite phases using NaH as a solid state reducing agent result in the formation of reduced phases which contain manganese centres with a constant average oxidation state of +2.5, thus leading to an empirical composition of La₁-ₓSrₓMnO₃-(0.5+x)/2. The structures of the reduced phases contain a 6-layer OOTOOT’ stacking sequence of the octahedral (O) and tetrahedral (T) sheets and so are closely related to the 4-layer OTOT’-stacked brownmillerite structure. Close inspection reveals that the structures of the La₁-ₓSrₓMnO₃-y (x = 0.67, 0.7 and 0.75) reduced phases contain an intralayer ordered arrangement of twisted tetrahedral chains, and are the first instances of refined 6-layer structures containing such an arrangement. The driving force dictating the arrangement of the twisted tetrahedral chains in these 6-layer structures are shown to be the size of the tetrahedral chain dipole moment and the coupling between neighbouring tetrahedral layers in a similar manner to the brownmillerite structure. This logic has been applied to rationalise the ordering arrangement of the twisted tetrahedral chains in other structures containing tetrahedral layers. Variable temperature neutron diffraction data reveal that the La₁-ₓSrₓMnO₃-y (0.67 ≤ x ≤ 0.83) reduced phases adopt magnetically ordered structures incommensurate with the nuclear structures below TN. In contrast, the structures adopted by reduced phases formed by topotactic reduction reactions of La₁-ₓCaₓMnO₃ (0.6 ≤ x ≤ 1) perovskite phases using NaH are split into 2 groups as a function of the La:Ca ratio: The reduction of perovskite phases in the range (0.6 ≤ x ≤ 0.8) result in the formation of reduced phases with an empirical composition of La₁-ₓCaₓMnO₂ which adopt structures containing a disordered arrangement of layers of edge-sharing MnO₆ octahedra and layers of vertex-sharing MnO₄ tetrahedra. In contrast, reduction of the perovskite phases in the range (0.9 ≤ x ≤ 1) result in the formation of reduced phases with an empirical composition of (La₁-ₓCₓx)0.5Mn<sub<0.5< sub="">O which adopt the rock salt structure with a disordered arrangement of the cations. The (x < 1) reduced phases are the first reported examples of extended oxides which contain manganese centres with an average oxidation state of below 2. Variable temperature neutron diffraction data reveal that the La₁-ₓCaₓMnO₃-y (x= 0.6, 0.67 and 0.7) reduced phases adopt G-type antiferromagnetically ordered magnetic structures below approximately TN ~ 220 K.</sub<0.5<> The structure of Sr₃Fe₂O₅Cl₂ is closely related to that of the A₃B₂O₇ n = 2 Ruddlesden-Popper structure. The topotactic reduction reaction of Sr₃Fe₂O₅Cl₂ with LiH results in the formation of the Fe(II) phase Sr₃Fe₂O₄Cl₂. Neutron powder diffraction data show that Sr₃Fe₂O₄Cl₂ adopts a body-centred tetragonal crystal structure with anion vacancies located within the central SrO layer of the phase. The structure of Sr₃Fe₂O₄Cl₂ is therefore a rare example of a structure consisting of infinite sheets of corner-sharing Fe(II)O₄ square planes. In addition, the effect of cobalt-doping on the magnetic properties of the isostructural Sr₃Fe₂-ₓCoₓO₄Cl₂ (0 ≤ x ≤ 1) series of reduced phases was investigated. Cobalt-doping was found to frustrate the antiferromagnetic order initially leading to a decrease in the magnetic ordering temperature but ultimately leading to spin glass behaviour.